Biocarbon from Pruning and Gardening Residues on The Santander University Campus, Using a Pirolisis System with Minimal Gas Emission - Livia, Walter Pardavé; Mantilla Suarez, Nadia Fernanda (Journal of Sustainability Perspectives, 2021)
A pilot – level system of the termal pirolisis process was developed to obtain biocarbon with minimal emission of polluting gases, from the solid waste generated in the pruning gases, from the solid waste generated in the pruning and gardening of the university campus of the University of Santander in Bucaramanga Colombia. The pilot – level system has a processing capacity of 50 kilograms of prunning and garden waste, and the operating variables ser 500ªC of temperatura and 120 minutes of processing. The prunnig and gardenning samples were divided into two. The first simple consisted of Woody-type residues (pruningn), the second simple consisted of grass and leat litter remains. The biocarbons obtaneid were characerized physicochemically, by close analysis and last chemical analysis (CHN). For its part, the morphology of the biocarbons and the microchemical anlysis of the ash particles that they possessed was carried out by means of scanning electron microscopy coupled with chemical microanalysis by means of X-ray dispersive energy spectroscopy. The biocarbon obtained can be used as soil additions to increase the forests that surrond the University campus.